RETAIL MARKET OF BANANA IN CURITIBA AND METROPOLITAN REGION - de CARVALHO, Ruy Inacio Neiva; CETNARSKI FILHO, Ricardo; MARTIN, Vinícius Caetano (Scientia Agraria, 2004)
The production of bananas (Musa spp.) in Paraná is growing and Curitiba and Metropolitan Area represent an important consumption area. This work aimed to characterize the retail market of bananas in Curitiba and Metropolitan Area in the period from February, 1999 to January, 2000. Four representative retail markets were selected and visited monthly for collection the information about cultivars presented, practiced prices (corrected to February, 1999), used packings, maturation stage and intensity of lesions in the peel of the fruits. Banana cultivars marketed in the studied period were ‘Nanicão’, ‘Prata’, ‘Maçã’ and ‘Ouro’. The cultivars ‘Prata’, ‘Nanicão’ and ‘Maçã’ were commercialized in 100%, 98% and 83% of the visits, respectively, and the cultivar ‘Ouro’ was found only in 16% of the visits. ‘Nanicão’ cultivar was marketed with the lowest average monthly price (from R$0,59 to R$0,81/kg) followed by banana ‘Prata’ (from R$0,98 to R$1,58/kg) and ‘Maçã’ (from R$1,54 to R$1,88/kg). The banana ‘Ouro’, although not present in the majority of visits, presented average price from R$1,36 to R$1,82/kg. The maturiry stage of ‘Nanicão’, ‘Prata’ and ‘Maçã’ showed a variation from 53 to 81% of yellow color of peel, while the cultivar ‘Ouro’ presented a variation from 50 to 100%. The banana market was realized with entire bunchs or clusters that were putted in bulk or hung in hooks. The lesions in the peel were classified as light and middle.